Echoes of Exodus : tracing a biblical motif - Estelle, Bryan D., 1959-; Estelle, Bryan D., 1959- (Downer's Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2018)
Israel's exodus from Egypt is the archetypal anvil on which Scripture shapes the language of deliverance. From the blasting furnace of Egypt, God leads Israel through the wilderness to Sinai and on to Zion. It is the story that illuminates the psalmist's poetry and inspires Isaiah's second-exodus rhapsodies. Exodus resonances pulse through the New Testament, from Jesus' birth to his death, from the letters of Paul to the Apocalypse of John. Bryan Estelle traces the motif through the canon of Scripture. He introduces us to the study of quotation, allusion, and echo, providing a firm theoretical basis for hermeneutical practice and understanding. --excerpts from back cover
Introduction -- Hermeneutical foundations -- The past is prologue: creation and exodus -- The exodus motif: a paradigm of evocation -- The psalms and the exodus motif -- Isaiah's rhapsody -- Exile and post-exile: the second exodus revisited -- Jesus as the new exodus in Mark and Matthew -- The exodus motif in Luke-Acts -- The exodus motif in Paul -- The exodus motif in 1 Peter -- The exodus motif in Revelation: redemption, judgment, and inheritance -- Conclusion -- Appendix: Intertextuality.
includes bibliographic material (pages 353-376).
includes indexes by author (pages 377-379), subject (pages 381-386) and scripture (pages 387-392).
Keywords: Bible. -- Theology; Exodus, The -- Intertextuality in the Bible; Exodus, The -- Typology